Gendering Dance - Anjali Gera Roy (Religions, 2020)
Originating as a Punjabi male dance, bhangra, reinvented as a genre of music in the 1980s, reiterated religious, gender, and caste hierarchies at the discursive as well as the performative level. Although the strong feminine presence of trailblazing female DJs like Rani Kaur alias Radical Sista in bhangra parties in the 1990s challenged the gender division in Punjabi cultural production, it was the appearance of Taran Kaur Dhillon alias Hard Kaur on the bhangra rap scene nearly a decade and a half later that constituted the first serious questioning of male monopolist control over the production of Punjabi music. Although a number of talented female Punjabi musicians have made a mark on the bhangra and popular music sphere in the last decade or so, Punjabi sonic production continues to be dominated by male, Jat, Sikh singers and music producers. This paper will examine female bhangra producers’ invasion of the hegemonic male, Sikh, Jat space of bhangra music to argue that these female musicians interrogate bhangra’s generic sexism as well as the gendered segregation of Punjabi dance to appropriate dance as a means of female empowerment by focusing on the music videos of bhangra rapper Hard Kaur.